Assessing the Knowledge of Breast Cancer and its Treatment Among Female Undergraduate Students in the Faculty of Science in a Tertiary Education Institution in Nigeria - Ahmed Alfa, Mustapha; Nasir, Abdulrahman; Wesley Hedima, Erick; David Agada, Emmanuel; Muhammad Sambo, Abdullahi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
A cross-sectional study carried out to determine the knowledge of breast cancer and its treatment among female undergraduate students in the faculty of science at Gombe State University. Self-administered questionnaires were distributed to all 260 respondents who were in the faculty of science Gombe State University. More than half of the respondents were aged 21-25 (59.2%), most of them were single (61.2%) and 70.4% of respondents reported having no family history of breast cancer and 38.1% were in 200 level. More than two-thirds of the respondents (85.0%) showed a poor understanding of the major risk factors and early warning signs of breast cancer but the result reported that the majority of the respondents are aware of the existence of the disease. Chi-square test detected a statistically significant association between academic level (p-value= 0.01<0.05), and family history (p-value= 0.04<0.05) with the knowledge of breast cancer and treatment. The findings show that there is inadequate knowledge of breast cancer disease among female undergraduate students in Gombe State University targeted education measures should be employed to improve the early detection of breast cancer.